2021
DOI: 10.3390/biom11081189
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Activin B as a Clinical Biomarker in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS)

Abstract: Reliable serum biomarkers are of immense need for diagnostic purposes of myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS)—a disabling and complex disease for which diagnosis is mainly based on clinical symptoms. The aim of this study was to evaluate a possible diagnostic potential of activin B by directly comparing 134 cases of ME/CFS with 54 healthy controls. Analyses of human activin B level in plasma samples were performed using a validated human activin B ELISA assay. The results of the study sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…There is a need for unbiased, specific diagnostic biomarkers for ME/CFS to expedite patient diagnosis and treatment, as some previously proposed biomarkers such as activin B are controversially discussed [ 164 , 165 ]. miRNA profiles represent a promising strategy to discover biomarkers and more recently to diagnose patients.…”
Section: Resultsmentioning
confidence: 99%
“…There is a need for unbiased, specific diagnostic biomarkers for ME/CFS to expedite patient diagnosis and treatment, as some previously proposed biomarkers such as activin B are controversially discussed [ 164 , 165 ]. miRNA profiles represent a promising strategy to discover biomarkers and more recently to diagnose patients.…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for these differences are unknown but may reflect differences in the genetic background of these individuals and/or variations in the case definition criteria used. However, a recent study by the same group using a different cohort of patients with ME/CFS (n = 134) reported no significant differences in activin B plasma levels between ME/CFS cases and controls (n = 54) (33). Thus, using activin B levels as a biomarker for ME/CFS remains controversial.…”
Section: Me/cfs Sera Induces T Fh Differentiation Of Naive Cd4 + T Cellsmentioning
confidence: 99%
“…In total, 56 of the studies recruited patients that met the FC [ 15 , 19 , 21 , 22 , 24 , 28 , 31 , 35 42 , 44 , 45 , 49 , 50 , 52 , 53 , 59 , 61 – 69 , 71 , 78 , 79 , 83 , 84 , 86 89 , 92 95 , 98 , 99 , 101 , 102 , 105 , 108 , 111 115 ]. Fourteen studies recruited patients that met the CCC [ 17 , 23 , 32 , 46 , 47 , 57 , 58 , 73 , 82 , 91 , 100 , 103 , 104 , 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were 13 studies that reported on endovascular/circulatory biomarkers (Additional file 2 , Table S4) [ 16 , 19 , 24 , 30 , 34 , 35 , 44 , 47 , 57 , 58 , 63 , 70 , 74 , 85 , 94 , 100 , 101 , 105 ]. Endothelial function was assessed in two studies [ 47 , 100 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation